2023
DOI: 10.3390/cells12151971
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Chlorella ohadii Photosystem II Reveals Protective Mechanisms against Environmental Stress

Maria Fadeeva,
Daniel Klaiman,
Ido Caspy
et al.

Abstract: Green alga Chlorella ohadii is known for its ability to carry out photosynthesis under harsh conditions. Using cryogenic electron microscopy (cryoEM), we obtained a high-resolution structure of PSII at 2.72 Å. This structure revealed 64 subunits, which encompassed 386 chlorophylls, 86 carotenoids, four plastoquinones, and several structural lipids. At the luminal side of PSII, a unique subunit arrangement was observed to protect the oxygen-evolving complex. This arrangement involved PsbO (OEE1), PsbP (OEE2), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It’s essential to note that a structurally similar component, the four-helix bundle PsbQ, is present in mature PSII, despite lacking sequence homology and exhibiting an opposite orientation ( Figure 8 , Burton-Smith et al., 2019 ; Fadeeva et al., 2023 ). During maturation, it is plausible that PsbQ substitutes Psb2 and acts as a template for the assembly of the extrinsic proteins PsbO and PsbP, thereby rendering its presence unnecessary in the mature PSII.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It’s essential to note that a structurally similar component, the four-helix bundle PsbQ, is present in mature PSII, despite lacking sequence homology and exhibiting an opposite orientation ( Figure 8 , Burton-Smith et al., 2019 ; Fadeeva et al., 2023 ). During maturation, it is plausible that PsbQ substitutes Psb2 and acts as a template for the assembly of the extrinsic proteins PsbO and PsbP, thereby rendering its presence unnecessary in the mature PSII.…”
Section: Resultsmentioning
confidence: 99%
“…Upon the dimerization of PSII monomers and subsequent attachment of LHCII trimers, the assembly process is finalized (Tokutsu et al, 2012). The ultimate Chlamydomonas PSII structure comprises up to 46 subunits (Sheng et al, 2021), which closely resembles the more comprehensive supercomplex identified in Chlorella ohadii (Fadeeva et al, 2023).…”
mentioning
confidence: 99%
“…Two distinct excitation pathways are operating: the productive pathway (A), which goes from P680 to QA, and the nonproductive pathway (B), which goes from P680 to pheophytin A409 (Figure 2). Remarkably, the two pheophytin molecules are placed at a similar distance to QA (9.7 Å), as is pheophytin A408 to QB (9.3 Å), yet the latter is not active in productive photoreduction [34]. This phenomenon could be attributed to the persistence of coherence in Branch A, while decoherence predominates in Branch B. QB-related slips have been recognized for some time [36].…”
Section: Femtosecond To Millisecond Coupling and Slipsmentioning
confidence: 99%
“…On the other hand, PSII must cope with potentially damaging events on the micro-to-millisecond timescale. In this case, extensive mechanistic slips, including internal cyclic electron transport, have evolved, some of which are species-specific [34]. The mechanistic couplings and interactions within PSII are exceptionally intricate, leading to a quantum efficiency of approximately 85% in While PSI operates via single electron events, PSII operates via two-electron reduction and four-electron oxidation steps.…”
Section: Femtosecond To Millisecond Coupling and Slipsmentioning
confidence: 99%
“…Each monomer of PSII contains approximately 20 subunits and over 60 cofactors and has a molecular weight of approximately 350 kDa. Structures of cyanobacterial PSII have been determined to resolutions of 1.85–1.95 Å with X-ray crystallography and cryo-EM. , Structures of eukaryotic PSII from plants, algae, and diatoms have been determined to resolutions of 2.5–5.3 Å with X-ray crystallography and cryo-EM. Our understanding of photosynthetic water oxidation has increased dramatically in the past decade because of advances in structural, computational, and biophysical methods (for recent reviews, see refs ).…”
Section: Introductionmentioning
confidence: 99%